VD_FINDINFO HC / 2012 / 566 vom 27. August 2012 - VD Tribunal cantonal (2012)
DROIT DE GARDE, RELATIONS PERSONNELLES, OBLIGATION D'ENTRETIEN | 176 al. 1 ch. 1 CC, 176 al. 3 CC, 273 CC, 308 CPC (CH), 317 CPC (CH)